Phage Biocontrol of Campylobacter jejuni in Chickens Does Not Produce Collateral Effects on the Gut Microbiota - Richards, Philip J.; Connerton, Phillippa L.; Connerton, Ian F. (Frontiers in Microbiology, 2019)
Bacteriophage biocontrol to reduce Campylobacter jejuni levels in chickens can reduce human exposure and disease acquired through the consumption of contaminated poultry products. Investigating changes in the chicken microbiota during phage treatment has not previously been undertaken but is crucial to understanding the system-wide effects of such treatments to establish a sustainable application. A phage cocktail containing two virulent Campylobacter phages was used to treat broiler chickens colonized with C. jejuni HPC5. Campylobacter counts from cecal contents were significantly reduced throughout the experimental period but were most effective 2 days post-treatment showing a reduction of 2.4 log10 CFU g-1 relative to mock-treated Campylobacter colonized controls. The administered phages replicated in vivo to establish stable populations. Bacteriophage predation of C. jejuni was not found to affect the microbiota structure but selectively reduced the relative abundance of C. jejuni without affecting other bacteria.